From Financial Decision-Making to Health Behavior: Financial Literacy as a Predictor of Physical Activity among Vocational Students - Putu Diah Asrida; I Gede Agus Adi Saputra (Politeknik Ganesha Medan, 2026)
Low levels of physical activity among adolescents have become an increasing global health concern, as they may influence the quality of future human resources. Previous studies have largely explained physical activity from environmental and psychological perspectives. However, cognitive–economic factors, particularly financial literacy, have received limited attention within the context of health-related behavior. This study investigates whether financial literacy can help explain variations in physical activity among vocational high school students. Financial literacy is examined through three dimensions: financial knowledge, financial behavior, and financial attitude. This explanatory quantitative research involved 296 students selected using stratified random sampling. The result show that each dimension of financial literacy shows a positive association with physical activity, with financial behavior emerging as the strongest predictor. These findings suggest that financial literacy extends beyond financial decision-making and may also play a role in shaping health-related behaviors. Financial literacy notably impacts physical activity in vocational high school students, with financial behavior as the key factor. Self-regulation and planning in financial management correlate positively with healthy behaviors, making financial literacy vital for promoting a sustainable adolescent lifestyle. The study offers an interdisciplinary perspective by highlighting how financial capability may contribute to the development of healthier lifestyle patterns among vocational adolescents. The novelty of this research lies in testing the self-regulatory spillover mechanism of financial literacy on physical activity of vocational high school students, which integrates financial literacy as a cross-domain psychological foundation to fill the gap between economic skills and consistency of a healthy lifestyle in adolescents.